(untitled) (Applied Biological Research, 2013)
The present study was aimed at to observe the changes in various clinico-physiological parameters in dogs subjected to different renal biopsy techniques. Eighteen mongrel dogs, divided randomly into 3 groups, were subjected to ultrasound-guided biopsy using 14-G Tru cut biopsy needle (group I), ultrasound-guided fine-needle aspiration biopsy using 18-G spinal needle mounted on 10 ml syringe (group II) and laparoscope-guided biopsy using laparoscopic biopsy forceps(group III). Post biopsy analysis of various parameters like rectal temperature, heart rate, respiration rate and skin fold tenting test revealed non-significant difference (P>0.05) at any post-procedural interval. This indicated that all these renal biopsy techniques in dogs were safe.